Violence and value intonomy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in philosophy at Massey University - Foulds, Steven (Massey University, 1990)
The central tenet of the thesis is that violence is a problem - a problem that has resisted solution primarily because we have habitually misconceived what it is about violence that makes it a problem. The thesis consequently offers an understanding of violence and, on the basis of this understanding, proposes a practical ethic designed to work against violence, while augmenting our moral power and general welfare, in human society. Part One is a factual analysis of violence in terms of what is called Value Intonomy. The aim is to show that reference to individual Value Intonomy explains what it is that makes violence harmful and, therefore, a problem. Ancillary hypotheses, on the addictive nature of violence and the integral nature of the problem of violence in human society, are appended to this part to complete the theory of violence offered. Part Two is an ethical analysis of violence in terms of what is called the Right to Value Intonomy Theory. This theory is explained, in the context of rights theories, and it is argued that violating the right to Value Intonomy is what makes violence morally wrong. It is then argued that recognising this Right, as the fundamental right of all moral agents, is a necessary condition for any ethic that is intended as being effective against violence. Finally, Part Three offers a Broad Consequentialism, based on the Right to Value Intonomy and called Renovation Ethics, as a practical solution to the problem of reducing violence and augmenting welfare in human society.
Keywords: Violence; Moral and ethical aspects